Teori Pembelajaran Kognitif dan Penerapannya Pada Buku Ajar Al’arabiyah Linnasyi’in di Ma Al-Huda Kota Gorontalo - Lahay, Mohamad; Ibrahim, Rabiatul Adawiyah; Ratni Bt. Hj. Bahri; Muh. Arif (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
Cognitive theory is a conceptual framework that is very relevant in the context of learning Arabic. The existence of language acquisition theory, meaningful learning, and cognitive individualism are crucial factors in achieving language learning goals. This study aims to understand the implementation of cognitive theory in learning Arabic at MA Al-Huda. The method applied is qualitative descriptive. Through this research, the author seeks to uncover the methods applied by Arabic language educators at MA Al-Huda, as well as the phenomenon of Arabic language learning by utilizing the theory, without intervention or substantial changes in its implementation. The results of the study show that the application of cognitive learning theory in Arabic language learning involves experiential reflection, guided free discussion, critical thinking development, problem solving, idea presentation, and concept exploration.